Maxillary unicystic ameloblastoma - Navarro, Cláudia Maria [UNESP]; Principi, S. M.; Massucato, Elaine Maria Sgavioli [UNESP]; Sposto, M. R. (British Inst Radiology, 2004)
The authors present the case of a 17-year-old White male patient complaining of enlargement in the gingival region and the fundus of the left maxillary anterior vestibular sulcus. The clinicopathological diagnosis was plexiform unicystic ameloblastoma. With this report, the authors illustrate the importance and complexity of a differential diagnosis of lesions with a cystic aspect in the anterior region of the maxilla, among them inflammatory radicular cysts, odontogenic keratocysts, adenomatoid odontogenic and unicystic ameloblastoma.
Keywords: ameloblastoma; unicystic; plexiform; cysts; maxilla; keratocyst